2018
DOI: 10.4236/as.2018.93020
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol Applied on Cotyledonal Leaves and Quality of Cucumber, Squash, Melon and Watermelon Seedlings

Abstract: The research was done to determine the effects of paclobutrazol (PBZ) through the dose of 150 mg•L −1 , on the quality of seedlings determined by the content of chlorophyll, height, leaf area, dry matter of roots and of the aerial part of cucumber, squash, melon and watermelon. Sowing of all species carried out on October 21, 2013 in polystyrene trays with 200 cavities filled with peat moss. Treatments were the doses of 150 mg of PBZ•L −1 water and the control (distilled water). The solution with PBZ and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…As a result of the measurements on the leaves of the seedlings, it was determined that in the chlorophyll content increased in the seedlings in the application group compared to the control group. In similar studies, it was found that paclobutrazol applied with foliar spray on melon seedlings increased the chlorophyll content in the leaves (Flores et al, 2018); besides, similar results were obtained from several species such as watermelon (Baninasab, 2009), Potato (Tsegaw et al, 2005) and lettuce (Akdemir, 2018). It was found that almost all of the different doses of Tebuconazole in melon seedling cultivation prevented excessive and unnecessary growth in seedling and stem lengths.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As a result of the measurements on the leaves of the seedlings, it was determined that in the chlorophyll content increased in the seedlings in the application group compared to the control group. In similar studies, it was found that paclobutrazol applied with foliar spray on melon seedlings increased the chlorophyll content in the leaves (Flores et al, 2018); besides, similar results were obtained from several species such as watermelon (Baninasab, 2009), Potato (Tsegaw et al, 2005) and lettuce (Akdemir, 2018). It was found that almost all of the different doses of Tebuconazole in melon seedling cultivation prevented excessive and unnecessary growth in seedling and stem lengths.…”
Section: Discussionsupporting
confidence: 53%
“…In a study conducted on eggplant, the tebuconazole applied at different doses significantly decreased the seedling length and stem length (Öztürk and Dursun, 2020). In a study on seedling quality of melon, 25 ppm paclobutrazol application was determined to suppress seedling length (Flores et al, 2018). In another study, the characteristics of tomato seedlings were investigated by applying paclobutrazol from the soil (1 ppm) and through foliar spray (25 ppm) at the stage where 2-4 true leaves were formed in tomato seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O Paclobutrazol (PBZ) the chemical name [(2RS, 3RS) -1 -(4-clorofenil) -4, 4-dimetil-2-(1, 2, 4-triazol-1-il) -pentano-3-ol] is one of the most effective triazole that inhibits gibberellin biosynthesis (Baninasab;Ghobadi, 2011). It is used to enhance seedling quality of tomato (Seleguini et al, 2013) and cucurbits (Flores et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The higher concentrations of PBZ caused a greater reduction than corresponding low concentrations. The inhibitory effect of PBZ on plant height has been reported in various crops such as tomato [28]; cucumber [26,27,42] squash, melon and watermelon [42]. Meanwhile, the foliar spray with 50 mg.L [28]; cucumber, melon and watermelon [42], olives [43], apple seedlings [24] and grapevines [44].…”
Section: Vegetative Growthmentioning
confidence: 99%